การระบุชนิดและการหารหัสดีเอ็นเอของซิลิเอตที่พบในทรายชายฝั่งทะเล ที่หาดลูกลม เกาะแสมสาร จังหวัดชลบุรี - สุชา เฉยศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Marine interstitial ciliates are a group of microeukaryotes constituting one of major components of benthic communities and playing crucial roles in nutrient cycling and regulation of bacterial and fungal populations. Given their importance, diversity of these ciliates has been less well explored comparing to freshwater and planktonic ones. In addition, accurate species-level identification of this particular group of protists is sometimes difficult and often requires help of experts. Using combined morphological and molecular data, biodiversity of marine interstitial ciliates in sand sediments collected during September 2011 to July 2012 from Look-Lom Beach, Samaesarn Island was investigated in order to 1) find a short DNA sequence or DNA barcode for determining species of ciliates dwelling in this beach and 2) evaluate the feasibility of using the DNA barcoding approach in identifying marine benthic ciliates in general. Sixty one morphospecies belonging to 29 genera were documented using light microscopy. Trachelocercid ciliates were the most abundant group and 13 morphospecies of them were recorded. Of all identified, 12 genera and 13 species, were reported for the first time in Thailand, suggesting unexplored diversity of the meiofaunal ciliates. Amplification and sequencing of ribosomal DNA, covering 18S, ITS1, 5.8S, ITS2, and partial part of 28S rDNA, giving the amplicons of about 2,900-3,600 bp were conducted for individually isolated cells of the examined 20 morphospecies from 12 genera. A total of 33 sequences were obtained and their full-length nucleotide compositions were analyzed to determine the most suitable portion as a DNA barcode for identifying species of marine interstitial ciliates studied. Of all 12 examined, nine could be identified correctly using a 500-600 bp fragment of the 18S rDNA sequences while the remaining three could be diagnosed accurately with the 500-600 bp portion comprising the ITS1, 5.8S, ITS2, and partial part of the 28S rDNA. Nucleotide sequence analysis of the proposed regions demonstrated high mean interspecific sequence divergences of 1.31-15.98% and low mean intraspecific ones of 0.00-3.91%, indicating the 500-600 bp barcoding regions of rDNA sequences as useful molecular signatures for distinguishing species of the studied taxa. This study not only pioneers the application of molecular tools in taxonomic identification of marine benthic interstitial ciliates but also provides the first comprehensive data on their biodiversity and underpins the need for more intensive and extensive investigations into biodiversity of marine benthic protists in Thailand.